Geopolítica de los minerales críticos: Dinámicas Globales y Retos Estratégicos - VEGA CENTENO GAMARRA, JOSE EMILIO (2025)
The geopolitics of critical minerals has become an issue of growing relevance in the current global context, where the transition towards sustainable energy sources and technological development, as well as important industries such as the military, depend largely on these resources. The demand for critical minerals has grown exponentially, with a market projected to reach $700 billion by 2040. However, the geographical concentration of their reserves and the control of processing by a small number of countries generate significant vulnerabilities in supply chains. These power dynamics redefine trade relations and national policies, closely linking the economy with national security. This paper aims to analyze the geopolitical importance of critical minerals, focusing on the global challenges and dynamics faced by the main international actors.